Analysis of Degradability of Blackberry (Rubus glaucus) Subjected to Different Storage Conditions - Teneda-Ramos, Eduardo (2024)
The purpose of this study was to assess how different storage conditions and types of containers affect blackberries (Rubus Glaucus), fruits that are particularly susceptible to post-harvest deterioration. Comparisons were made between two temperature conditions: room temperature (19 °C) and refrigeration (4 °C), and three types of container materials: low-density polyethylene (LDPE), polypropylene (PP), and polylactic acid (PLA). The findings indicated that refrigeration is the most effective strategy for maintaining the quality of blackberries during storage. This method significantly preserved the weight and stability of the fruit, with PLA standing out in this respect. Additionally, a considerable reduction in microbial activity was observed under refrigeration, with LDPE proving to be the most effective at inhibiting mold growth. These results underscore the importance of properly controlling both temperature and container materials type to extend shelf life and preserve the quality of blackberries, which is crucial not only for the food industry, where maintaining freshness and flavor is imperative, but also for consumers who seek high-quality fruit products.